2007
DOI: 10.1080/02786820601160549
|View full text |Cite
|
Sign up to set email alerts
|

First LDA Measurements of Nanoparticle Velocities in a Low-Pressure Impacting Jet

Abstract: The velocity of nanoparticle agglomerates and 1 μm latex spheres approaching an impaction surface from a free gas jet was measured by LDA at pressures of 7.4 and 1.8 kPa, respectively. The "aerodynamically transparent" carbon nano-agglomerates gave sufficient LDA signal while the drag force was dominated by the size of the individual primary particles (diameter about 11 nm). The particle velocity as a function of distance from the impaction plate was also modelled on the basis of a CFD simulation of the flow f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…While the gas velocity profile in such low-pressure impactors (LPI) has been investigated thoroughly in simulations and experiments [4][5][6], only fluid dynamic calculations are available for the particle velocity profile. The first direct measurements of the particle velocities by laser Doppler anemometry (LDA) on specially structured nanoparticles have been recently performed [7]. Thus far, these results support the assumption, which has been made generally since the work of Marple [4], that the particle velocity at impact is ca.…”
Section: Background Theorymentioning
confidence: 59%
“…While the gas velocity profile in such low-pressure impactors (LPI) has been investigated thoroughly in simulations and experiments [4][5][6], only fluid dynamic calculations are available for the particle velocity profile. The first direct measurements of the particle velocities by laser Doppler anemometry (LDA) on specially structured nanoparticles have been recently performed [7]. Thus far, these results support the assumption, which has been made generally since the work of Marple [4], that the particle velocity at impact is ca.…”
Section: Background Theorymentioning
confidence: 59%
“…By varying the nozzle flow velocity via the pressure in the impaction chamber from about 30 to 300 m/s, one can adjust the impact velocity (ca. 85% of mean nozzle exit velocity [ 16 ]) and hence the degree of fragmentation.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent calculations by Li and Wang showed that a transition to pure specular reflection occurs for very small nanoparticles leading to a reduced friction force 3) . Even stronger deviations from the Cunningham correction were observed in direct measurements of the velocity of nanoparticles in rectilinear acceleration by means of Laser Doppler Anemometry (LDA) 4) . However, no systematic investigation of the drag coefficient for nanoparticles at large mean free paths has been undertaken so far.…”
Section: Introductionmentioning
confidence: 99%